2009
DOI: 10.1186/1756-9966-28-87
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hodgkin lymphoma response evaluation with MRI texture classification

Abstract: Background: To show magnetic resonance imaging (MRI) texture appearance change in nonHodgkin lymphoma (NHL) during treatment with response controlled by quantitative volume analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 34 publications
(29 reference statements)
0
32
0
Order By: Relevance
“…Third, GLCM continue to outperform other methods of texture classification [27]. Fourth, these quantitative imaging features have been shown to improve tumor diagnosis [11, 14], and to provide measures of response assessment [28, 29] and radiation-induced gland injury [30], and are reproducible across multiple imaging units [31]. Lastly, and perhaps most relevant to the present study, recent investigations have shown that CT texture relates to fibrosis staging [15, 16] so the extension to liver insufficiency is not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Third, GLCM continue to outperform other methods of texture classification [27]. Fourth, these quantitative imaging features have been shown to improve tumor diagnosis [11, 14], and to provide measures of response assessment [28, 29] and radiation-induced gland injury [30], and are reproducible across multiple imaging units [31]. Lastly, and perhaps most relevant to the present study, recent investigations have shown that CT texture relates to fibrosis staging [15, 16] so the extension to liver insufficiency is not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…The texture parameters were derived, respectively, from image histogram (information about the intensity of pixels and without any spatial relations between the pixels on the image), gradient (information about the image intensity distribution and describes the histogram of the absolute gradient values of 3 Â 3 neighborhoods of pixels in the ROI), run-length matrix (information about pixel runs with the specified gray-level values in a given direction and describes intensity homogeneity in specific directions in the ROI), co-occurrence matrix (information about changes of SI with increasing distance, describes the gray-level value distribution of pixel pairs along all directions at different distances in the ROI), autoregressive model (description of texture based on the statistical correlation between neighboring pixels), and wavelet transform (information about the frequency of similar SIs and describes the wavelet transform of the pixels in the ROI) (16,18,21).…”
Section: Conventional Imaging Analysismentioning
confidence: 99%
“…TA allows the computation of hundreds of texture features based on the SI of pixels in the ROI (15,16), which may yield potential information. Successful applications of TA have been reported in discriminating pathologic stages of hepatic fibrosis (15) and glioma (17), differentiating invasive ductal carcinoma from invasive lobular carcinoma (18) and hepatic cysts from hemangiomas (19), evaluating the therapeutic efficacy of metastatic RCC (20), non-Hodgkin lymphoma (21), and mammary carcinomas (22). Moreover, TA can be performed with commercial software and does not require highly specialized computer knowledge.…”
mentioning
confidence: 99%
“…There is currently considerable interest in probing intralesional heterogeneity by evaluating the intensity of acquired imaging voxels (termed texture analysis) [18]. Textural analysis is being applied to predict treatment response on CT [19], PET imaging and both conventional [20] and dynamic contrast-enhanced MRI [21,22].…”
Section: Tumour Response Assessment Using Imagingmentioning
confidence: 99%